Increased carbon transport in the Hudson River: unexpected consequence of nitrogen deposition?. Issue 3 (1st April 2005) - Findlay, Stuart EG
Abstract : Dissolved organic carbon (DOC) is the major form of organic matter transported by large rivers and represents an important movement of carbon from terrestrial to coastal systems. Concentrations of DOC in New York's Hudson River have doubled over the past 16 years, implying a substantial increase in net movement of organic carbon from the watershed to New York Harbor and Bight. During the same time period there has been a decline in net consumption of DOC during travel through the tidal freshwater portion of the Hudson. This reduced removal of DOC amplifies the apparent increased load of DOC from the Hudson's watershed, resulting in an overall doubling of DOC delivery to the lower reaches. Either factor changing in isolation could cause a substantial increase in carbon delivery, but the two acting in concert suggest a fundamental change in processes supplying carbon to surface waters. Temperature, water yield, and land cover have not changed in ways that would make these viable causes for the altered DOC. One plausible mechanism driving both of these changes is a soil microbial response to nitrogen deposition, resulting in greater export of humic material. Other surface waters draining regions receiving continued high rates of nitrogen deposition may be undergoing similar, currently undetected shifts in quantity and composition of carbon in transport.